Regulation of genes involved in carnitine homeostasis by PPARa across different species (rat, mouse, pig, cattle, chicken, and human) - Ringseis, Robert; Wen, Gaiping; Eder, Klaus; Justus Liebig University Giessen (My University, 2012)
Recent studies in rodents convincingly demonstrated that PPAR-alpha is a key regulator of genes involved in carnitine homeostasis, which serves as a reasonable explanation for the phenomenon that energy deprivation and fibrate treatment, both of which cause activation of hepatic PPAR-alpha, causes a strong increase of hepatic carnitine concentration in rats. The present paper aimed to comprehensively analyse available data from genetic and animal studies with mice, rats, pigs, cows, and laying hens and from human studies in order to compare the regulation of genes involved in carnitine homeostasis by PPAR-alpha across different species. Overall, our comparative analysis indicates that the role of PPAR-alpha as a regulator of carnitine homeostasis is well conserved across different species. However, despite demonstrating a well-conserved role of PPAR-alpha as a key regulator of carnitine homeostasis in general, our comprehensive analysis shows that this assumption particularly applies to the regulation by PPAR-alpha of carnitine uptake which is obviously highly conserved across species, whereas regulation by PPAR-alpha of carnitine biosynthesis appears less well conserved across species.
Keywords: PPAR-alpha; carnitine homeostasis; animal studies; carnitine uptake; carnitine biosynthesis; ddc:570